Misperceptions and Attitudes Towards Plant-Based Eating in Inner-City Patients With Advanced Kidney Disease. (14th June 2022) - Wei, Lulu; Bae, Edward; Canning, Caroline; Martinez-Machado, Sasha; Gidon, Ariel; Sherman, Brett; Markell, Mariana
Abstract: Objectives: PBE may result in healthier eating in both patients on hemodialysis and those with other advanced kidney diseases, with increased phosphorous and potassium allowances as well as lower acid load. Understanding interest in and beliefs regarding plant based eating (PBE) in an underserved inner-city pt population with kidney disease may help tailor healthier eating plans based on PBE. Methods: A random sample of 33 dialysis and 22 kidney transplant pts in an inner-city environment were surveyed regarding beliefs about PBE and dietary intake by 24-hour recall using the ASA24 database. Results did not differ between populations so they were analyzed together. Not all pts completed all questions. Results: Mean age was 55.3 ± 2.1 yrs, 54% male (30); 88% (49) identified as Black, 36% US-born (20); 77% (30) reported annual income <$40K,  64% (35) did not finish college. 8/28 (29%) reported having tried PBE, and 22/39 (57%) were interested. 52% of patients (29) reported not having been recommended PBE before. Recommendations were more likely to have come from a friend or acquaintance and not a doctor or nutritionist (23 vs 4, p = 0.048). Willingness to try PBE in the future was associated with belief that diet changes can improve kidney health (p = 0.031), that PBE can improve kidney health (p = 0.002), and that eating less meat would improve hypertension (p = 0.031) or diabetes (p = 0.034). Pts who previously tried PBE were more likely to believe PBE can improve hypertension (p = 0.045). Pts who believed PBE would worsen hypertension were more likely to be receiving SNAP benefits (r = 0.44, p = 0.032), and be eating more servings of starchy vegetables (p = 0.011), poultry (p = 0.041) and milk (p = 0.011). Conclusions: In our population, recommendations for PBE were more likely to come from non-healthcare professionals. Although fewer than a third had tried PBE, more than half of patients surveyed would be willing to try PBE, which was related to beliefs in it's value. As patients at highest risk for food insecurity were less likely to have tried PBE and given that PBE may be protective against kidney disease progression and improve cardiovascular risk factors, it is imperative that health professionals refer patients for nutrition counseling regarding all aspects of PBE, and that counselors in these areas understand misperceptions in order to help alleviate disparities in care. Funding Sources: Unfunded.